Genome-Wide Homozygosity Mapping Reveals Genes Associated With Cognitive Ability in Children From Saudi Arabia - Kornilov, Sergey A.; Tan, Mei; Aljughaiman, Abdullah; Naumova, Oxana Yu; Grigorenko, Elena L. (Frontiers in Genetics, 2019)
Recent studies of the genetic foundations of cognitive ability rely on large samples (in extreme, hundreds of thousands) of individuals from relatively outbred populations of mostly European ancestry. Hypothesizing that the genetic foundation of cognitive ability depends on the broader population-specific genetic context, we performed a genome-wide association study and homozygosity mapping of cognitive ability estimates obtained through latent variable modeling in a sample of 354 children from a consanguineous population of Saudi Arabia. Approximately half of the sample demonstrated significantly elevated homozygosity levels indicative of inbreeding, and among those with elevated levels, homozygosity was negatively associated with cognitive ability. Further homozygosity mapping identified a specific run, inclusive of the GRIA4 gene, that survived corrections for multiple testing for association with cognitive ability. The results suggest that in a consanguineous population, a notable proportion of the variance in cognitive ability in the normal range in children might be regulated by population-specific mechanisms such as patterns of elevated homozygosity. This observation has implications for the field’s understanding of the etiological bases of intelligence and its variability around the world.